Evolução de frascos reacionais fechados para digestão assistida por radiação micro-ondas - Garitta, Julia de Alencar (Universidade Federal de São Carlos, 2022)
Modern instrumental methods often require complete digestion of the sample before elemental analysis, where all organic content has been removed and the analytes of interest are available in solution. These sample decomposition processes that precede the instrumental measurements are crucial steps for their preparation, as they demand cost, time, handling and eventual errors, therefore, this preparation step should be as simplified and safe as possible. One of the several sample preparation techniques used in wet and closed systems are microwave radiation assisted systems, which are an advantageous strategy since, as they are usually performed in closed system, they guarantee isolation from the laboratory atmosphere, minimizing possible contamination and losses in the reaction medium. They also offer the possibility of employing high temperatures and pressures and, as an additional benefit, require shorter digestion times compared to procedures involving conductive heating. The microwave radiation directly heats the liquid phase and the vapors derived from the reaction mixture do not absorb the radiation and thus are condensed on the cold walls of the digestion vessel, as the temperature in its gas phase in lower than the temperature in the liquid phase. The vessels used in the system are a key point for the efficiency of digestion by microwave radiation and there are some essential parameters that must be considered so that they work more efficiently and in a safer way. The first parameter is that the vessel must be composed of an inert material, resistant to high temperatures and pressures, acid mixtures in high concentrations and that is also totally transparent to microwave radiation so that it does not affect the accuracy of the analysis. Thus, Polytetrafluoroethylene (PTFE), Perfluoroalkoxy (PFA) and Tetrafluorometoxyl (TFM®) are the most commonly used materials. Another important factor related to the safety of the system is the possibility or not of having pressure relief in the vessel, with the presence or absence of a valve to relieve excess pressure or vessels with or without a rupture membrane. Other parameters such as volume, design, durability, performance and cost of the vessels are also key points that must be evaluated so that the sample digestion step is increasingly efficient making laboratory conditions faster and safer, while allows the system to reach high temperatures and pressures, optimizing digestions. Based on these parameters, this study aims to present and discuss the principles of microwave-assisted digestion using closed vessels and their evolution, approaching the performance of current technology and the desirable performance.
Evolution of closed reactional vessels for microwave-assisted digestion
Keywords: Radiação micro-ondas; Preparo de amostras; Frascos reacionais fechados; Digestão eficiente; Microwave radiation; Sample preparation; Closed reaction vessels; Efficient digestion; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA